Two high schools and the road to full inclusion: A comparison study. (November 2013) - Pierson, Melinda R; Howell, Erica J
This article documents a roadmap for developing fully inclusive school sites at the secondary level. Full inclusion is defined as placement in the general education classroom for all students with disabilities. Specifically, two large high schools located in suburban areas attempted to fully include over 300 students identified as needing special services. Students had varying disabilities, but each school attempted to fully include every student. Although one school was an established high school and the other was brand new, both experienced similar benefits and challenges when transitioning to a full inclusion model. This article aims to share specific strategies which contributed to the success of full inclusion at each school site and to discuss challenges that arose during planning and implementation.